The intention to adopt electronic publishing: A case of Malaysian publishers / Zahril Shahida Ahmad - Ahmad, Zahril Shahida (Institute of Graduate Studies, UiTM, 2018)
In the modern era of ICT revolution, the application of electronics to every aspect of human life has become significant. Electronic publishing has emerged as a major development in the media landscape and the adoption of this new media has become an important area of research. The continuance of electronic publishing depends on the adoption of this media by publishers and users. However, a research demonstrates that the rate of adoption of electronic publishing amongst Malaysian publishers is low. In addition, an audit report from 2011 journal in Malaysia revealed that 62.9% of Malaysian journals are still produced only in print format, while only 31.3 % are produced hybrid format (both print and electronic online), only 5.8 are born digitally exclusively on the Internet. It seems that electronic publishing has not penetrated successfully in Malaysian markets. The five main objectives of this study are: 1) to solicit problems faced by Malaysian publishers in adopting electronic publishing; 2) to determine technological factors that facilitate the intention to adopt electronic publishing amongst Malaysian publishers; 3) to determine organisational factors that facilitate the intention to adopt electronic publishing amongst Malaysian publishers; and 4) to determine environmental factors that facilitate the intention to adopt electronic publishing amongst Malaysian publishers. A research model is developed to identify and evaluate the key determinant factors influencing the intention to adopt electronic publishing amongst Malaysian publishers. This study draws on the organisation adoption theory, that is, the technology, organisation, and environment framework (TOE) to understand and explain the determinant factors of electronic publishing adoption…